Nilai - Nilai Yang Terkandung Di Dalam Tradisi Tedak Siten(Turun Tanah) Desa Pematang Duku Timur Kecamatan Bengkalis - Nur adila zulf; Siti khodijah (CV. Alim's Publishing, 2023)
The purpose of this research is to find out what are the values contained in the traditional tedak siten (down the ground) traditions in Pematang Duku Timur village, Bengkalis sub- district, this research is a qualitative research that focuses on the values ​​contained in the traditional tedak traditions. siten. The source of this data came from religious leaders, the community and village midwives in the village of Pematang Duku Timur. Data collection techniques used interviews and documentation. data analysis includes data collection, data reduction, data display and conclusion verification. The results of his research are the values ​​contained in the tedak siten tradition in Pematang Duku Timur, Bengkalis sub- district, namely: the value of tolerance, the value, the value of strengthening silaturrahmi ties, the value of endeavor, the value of strengthening family relationships, the value of love for the Prophet, then the value of gratitude.